A Need For Responsible Risk Assessment In Formulating Public Policy A Case Study: Crystalline Silica - Barry A. Hillman (Society for Mining, Metallurgy & Exploration, 1992)
Respirable (PM-10) crystalline silica is regulated by the State of California as a carcinogen. The risk-management of this material by the State exemplifies the inherent problems in the development of regulations based on current risk-assessment practices. The influence of extremely conservative risk-assessment and risk-management can be expressed in economic impacts including the increased cost of production, reduced competition, increased prices, reduced employment and redistribution of income. This paper attempts to contrast theoretical risk- assessment and risk-management with current application using crystalline silica as an example. Based on health information pertaining to silica, the paper examines federal and State of California regulatory and public policy positions. Using current risk factors and empirical data for the Central Valley of California, the projected incidence of lung cancer in humans is examined. While such an analysis would project an extremely high incidence of lung cancer as well as silicosis, not a single case of either lung impairment has been recorded within the study area or throughout the world in the general population. This suggests that sound guidelines for the analysis of scientific information have given way to the assumption that virtually any information representing a substance as a carcinogen is to be considered valid with little or no qualification.